Impatiens Arriensii (Zoll.) T. Shimizu (BALSAMINACEAE) JENIS ENDEMIK DARIPULAU MADURA - Nanda Utami (BERITA BIOLOGI, 2000)
Impatiens arriensii (Zoll.) T.Shimizu is endemic to Madura island. This species is confined only to certain locations on this island.It is remarkable in having four locular ovary with the fusing together of all four lateral petals.The populations of I.arriensii in Madura island was found to be extinct in 1999, (presumably) due to the habitat disturbance.Detailed description and illustration are provided.